Penetapan Metode Uji Daya Hantar Listrik untuk Benih Sorgum (Sorghum bicolor L.) - Khodratien Fatonah; Nalwida Rozen (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2017)
The objective of this experiment I was to determine accurate combinations of water volume and amount seed of the electrical conductivity test for seed vigor test in sorghum. Completely Randomized Design of 15 seed lots with 3 replications were used to determine electrical conductivity method with different vigor. The variable were observed: standard germination, field emergence, speed of germination, first count, conductivity, potassium leachate and eight combination conductivity method of water volume (50, 100, 150 and 200 ml) and amount of seed sorghum (50 and 75 seed count). The result of this experiments showed that electrical conductivity test method with 150 ml water volume and 75 seed count was accurate and suitable for sorghum seed vigor test